2016
DOI: 10.1108/lhs-04-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Leading change: introducing an electronic medical record system to a paramedic service

Abstract: (2016) Leading change: introducing an electronic medical record system to a paramedic service. Leadership in Health Services, 29 (2). pp. 136-150. The adoption use of EMR by in the emergency medical and ambulance setting is expected to provide across the health sector is a significant innovation providing wide-ranging benefits, but there is little research into processes of adoption in this sector. it remains little studied especially in the emergency medical and ambulance setting. This study examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Studies examining implementation and adoption suggested that EMS agencies are adopting EHRs primarily for quality purposes, including quality assurance and quality improvement, as well as for billing purposes. 49,50,57 Other themes mentioned by one study each were workforce training needs analysis and education, 57 and reduced data loss and state mandates requiring services to adopt EHRs. 49 Barriers to EHR adoption included financial, organisational, technical and privacy/security reasons, fears of increasing run times, difficulty integrating EHRs with existing systems and difficultly in complying with legal mandates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies examining implementation and adoption suggested that EMS agencies are adopting EHRs primarily for quality purposes, including quality assurance and quality improvement, as well as for billing purposes. 49,50,57 Other themes mentioned by one study each were workforce training needs analysis and education, 57 and reduced data loss and state mandates requiring services to adopt EHRs. 49 Barriers to EHR adoption included financial, organisational, technical and privacy/security reasons, fears of increasing run times, difficulty integrating EHRs with existing systems and difficultly in complying with legal mandates.…”
Section: Discussionmentioning
confidence: 99%
“…All participants in Baird and Boak's 50 research suggested that additional formal training may have aided earlier adoption, and the majority (79%) found informal learning from peers to be very helpful or somewhat helpful. Both Landman et al's 49 and Baird and Boak's 50 findings highlight the importance of support and training in aiding adoption.…”
Section: Strategies To Support Implementationmentioning
confidence: 99%
See 3 more Smart Citations